2019
DOI: 10.1038/s41598-019-56574-w
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Medical Conditions as Predictors of Overall Survival in Glioblastoma Patients

Abstract: Glioblastoma (GBM) is an aggressive central nervous system tumor with a poor prognosis. This study was conducted to determine any comorbid medical conditions that are associated with survival in GBM. Data were collected from medical records of all patients who presented to VCU Medical Center with GBM between January 2005 and February 2015. Patients who underwent surgery/biopsy were considered for inclusion. Cox proportional hazards regression modeling was performed to assess the relationship between survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Genetic mutations and molecular tumor markers became integral part of GBM assessment in modern neuro-oncology [ 22 ]. Nowadays, the well-known genetic mutations like O6-methylguanine methyltransferase (MGMT) promoter methylation, which is associated with a significantly higher median survival after therapy with TMZ [ 23 ] and other molecular tumor biomarkers, such as epidermal growth factor receptor (EGFR) amplification, aldehyde dehydrogenase 1A3 (ALDH1A3) and isocitrate dehydrogenase (IDH1/IDH2) isoforms are currently foci of research and were also linked to prognosis [ 22 , 24 ]. Limited data exist on the prevalence of DM2 among patients with GBM.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic mutations and molecular tumor markers became integral part of GBM assessment in modern neuro-oncology [ 22 ]. Nowadays, the well-known genetic mutations like O6-methylguanine methyltransferase (MGMT) promoter methylation, which is associated with a significantly higher median survival after therapy with TMZ [ 23 ] and other molecular tumor biomarkers, such as epidermal growth factor receptor (EGFR) amplification, aldehyde dehydrogenase 1A3 (ALDH1A3) and isocitrate dehydrogenase (IDH1/IDH2) isoforms are currently foci of research and were also linked to prognosis [ 22 , 24 ]. Limited data exist on the prevalence of DM2 among patients with GBM.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Chaichana et al on 182 patients with low-grade gliomas (WHO grade (ii)) reported that constant hyperglycemia resulted in a decrease of treatment efficacy, with consequent decrease of patient survival and increased tumor recurrence [ 85 ]. Analogous results were obtained examining patients with high-grade gliomas and glioblastoma, so that patients with glioblastoma and diabetes showed a worse prognosis [ 86 , 87 , 88 ]. These observations suggested the potential beneficial effects of drugs lowering blood glucose concentration in the treatment of glioma.…”
Section: Metforminmentioning
confidence: 67%
“…Previous research examining individual medical comorbidities in GBM patients of all ages found that specific comorbidities asthma and hypercholesterolemia were related to decreased survival, however, these comorbidities were present in less than 10% of their study population, and further research confirming these findings is needed. 17 A recent review of the literature found that the presence of hyperglycemia, rather than diabetes, was an independent risk factor for poor outcome and shorter OS in patients with GBM. 18 Liu et al found that lower systolic blood pressure, lower albumin, and higher blood glucose were associated with worse survival.…”
Section: Discussionmentioning
confidence: 99%